Editorial - Ahmed, Tahera (Bangladesh Journal of Bioethics, 2015)
Greetings to all our Readers and Authors! The Bangladesh Journal of Bioethics is gaining more popularity among all of us who are concerned about standards, norms, practices and ethics. This journal is our voice to share what is being practiced and what should be done. It will help to bring about equality and equity through an ethical rights based approach in all sectors of development touching our lives. This issue contains articles on diverse aspects of medical and social practices and will be very useful in ensuring that Bioethical standards are complied with.